The criminal protection of digital evidence in criminal and civil matters: A comparative study - Ehjelah, Abdullah; Zaitoun, Maamoun Abu; Obeidat, Yusuf; Issa, Hamzeh Abu; Almanasra, Majd Waleed (Research Journal in Advanced Humanities, 2026)
This study addresses the topic of the criminal protection of digital evidence in matters of criminal and civil law. It does so by explaining the criminal procedures that must be observed to protect this evidence and detailing the legal provisions that criminalize and penalize acts of assault on digital evidence in comparative laws. The importance of this study lies in the fact that countries worldwide are currently moving toward the use of information technology in various fields. Information technology is now widely employed in contract execution, communication, and digital transactions, all of which are inevitably accompanied by digital evidence. Crimes involving this technology may arise, which are difficult to prove without the existence of digital evidence, thus necessitating special criminal protection for such evidence. The problem addressed by this study stems from a legislative shortfall in some comparative laws, which is represented by the narrow scope of criminal protection for digital evidence. This shortfall includes the requirement of specific characteristics in the perpetrator for the crime of assault on this evidence, as well as restricting substantive protection to digital evidence related only to crimes specified in electronic laws. Additionally, the problem includes the absence of protection for digital evidence related to civil matters. This study relied on the analytical and comparative approaches and reached several conclusions, most notably: There is suitable procedural criminal protection for digital evidence in comparative laws. There is also appropriate substantive criminal protection for digital evidence in Jordanian and Palestinian law, but the scope of substantive protection for digital evidence is limited under Emirati law. The study offers several recommendations, the most prominent of which is the addition of provisions to some electronic crime laws that expand the scope of substantive protection for digital evidence.